Influence of topographic and edaphic factors on vulnerability to soil degradation due to cattle grazing in humid tropical mountains in northern Honduras - Blanco Sepúlveda, R.; Nieuwenhuyse, A. (2015)
Low altitude humid tropical mountains in Central America have experienced a process of livestock expansion during recent decades. However, the use of sloping areas for cattle grazingmay lead to significant soil degradation and thereforewe examined the influence of the slope gradient on soil degradation in pastures in a humid tropical mountainous area in northern Honduras. Understanding this relationship permits estimates of the physical carrying capacity of the soil, which in turn may help to improve livestock use within the study area. Variables examined included soil bulk density,texture, organicmatter content and consistency aswell as visual indicators of soil and vegetation degradation. There is a significant positive correlation between the bulk density as a proxy for soil degradation and slope gradient. Furthermore, itwas foundthatwhen soils arewater-saturatedgrazing leads to severe degradation. Togetherwith visual indicators, these data showthat paddockswith slopes less than 30% have a carrying capacity between 900 and 1900 Animal Units (AU) ha−1 year−1 andmany are currently underutilized. Paddocks with slopes between 30 and 50% have a carrying capacity between 400 and 600 AU ha−1 year−1. Paddocks with slopes over 50% have the lowest carrying capacity: less than 200 AU ha−1 year−1. The latter are frequently over-used; most of them show clear signs of soil and vegetation degradation. Land use in these areas needs to change or their grazing management needs to be reorganized to adjust actual stocking rate to physical carrying capacity of the soils to prevent further degradation.